Analysis of Article 28I Paragraph (4) of the 1945 Constitution on the Protection of Minority Rights and the Principle of Non-Discrimination in the Indonesian Legal System - Priyana, Yana; Sopian, Sopian (West Science Law and Human Rights, 2025)
This paper examines Article 28I Paragraph (4) of the 1945 Constitution of the Republic of Indonesia from a normative juridical perspective, focusing on its role in protecting minority rights and upholding the principle of non-discrimination. As a constitutional provision, Article 28I (4) mandates the state—particularly the government—to ensure the protection, promotion, enforcement, and fulfillment of human rights. The study analyzes how this mandate is reflected in national laws, judicial decisions, and administrative practices, while also assessing Indonesia’s compliance with international human rights obligations. The findings reveal that despite strong constitutional commitments, the implementation remains inconsistent due to inadequate enforcement, the absence of a comprehensive anti-discrimination law, and the persistence of discriminatory local regulations. The study recommends legal harmonization, institutional strengthening, and the enactment of specific anti-discrimination legislation to ensure equal rights for all citizens, especially minorities. This research contributes to the development of a more inclusive and just legal framework in Indonesia.